Pendidikan Anak Usia Dini Menurut Pandangan Maria Montesorri - Mukhsin Mukhsin; Khurin In Ratnasari; M Bustanul Ulum (Program Studi PGMI, IAI Al-Falah As-Sunniyyah Kencong, 2019)
Children have or strength in themselves to develop themselves, have a natural desire to learn and work, together with a strong desire to get pleasure. Children prefer to do activities than just being entertained or pampered. Children will always look for something new to do that is something that has more difficult and challenging levels. In addition, children also have the desire to be independent. Montessori class is one of the first to emphasize a warm and comfortable environment in child-based learning. Montessori learning is very suitable for children learning through hands-on activities, in preschool years is a time where the brain development of children is still good and parents become friends in their learningKeywords: Education, Children, Maria Montesorri.